SIMULATION OF NATURALLY FRACTURED RESERVOIRS USING SINGLE-POROSITY EQUIVALENT MODELS - Saalfeld, Robison Quintana (2017)
Brazilian Pre-Salt reservoirs are composed of very heterogeneous carbonate rocks with high permeability layers. Double-porosity models are usually applied for the simulation of such systems. In double-porosity models, the rock matrix and the fractures are idealized as two different porous media, modeled as two spatially coincident grids related by a transfer function. However, double-porosity models require solving more equations and, consequently, demand more computational time to simulate than conventional single-porosity reservoir models. An alternative to simulate heterogeneous reservoirs more efficiently is to use pseudo properties that account for both media in a single-continuum equivalent model. This work presents a methodology to obtain similar results of double-porosity models through the use of conventional single-porosity reservoir models with pseudo properties. The methodology is applied to 280 homogeneous isotropic models composed by different combinations of properties, classified accordingly to characteristic naturally fractured reservoir parameters. For 97% of the tested models, the methodology was able to obtain single-porosity equivalent models that resemble the behavior of double-porosity with error below 10%. For the availed cases, the use of single-porosity models implies a reduction of up to 33 times in computational time, which may allow more studies in order to obtain better reservoir management.